Staged resection for vestibular schwannoma. (September 2015) - Kunimoto, Yasuomi; Lauda, Lorenzo; Falcioni, Maurizio; Taibah, Abdelkader; Hasegawa, Kensaku; Sanna, Mario
Abstract Conclusion: Surgery remains the preferred option for large vestibular schwannoma (VS). The presence of unpredictable intraoperative difficulties may convince the operator to suspend the surgery to avoid risks to patient life. Additional surgeries may be mandatory and are better performed using a transcochlear approach. High rates of complications, poor facial nerve results, and a percentage of incomplete removals should be expected in such unfavorable cases. Objectives: To review the results for nine cases of huge VS treated by staged resection. Method: A retrospective case review was performed for all nine patients who underwent staged resection of VS at the Gruppo Otologico between 1984–2012. The decision to perform staged surgery was always made intra-operatively after encountering unpredicted difficulties. Results: The nine patients represented 0.3% of all patients who underwent VS surgery during the same period. Mean tumor size was 4.7 cm (range = 3.0–6.6 cm). Two cases required three surgeries, resulting in a total of 20 operations. In addition, two cases required pre-operative ventriculoperitoneal shunt and one required temporary tracheotomy. After the final stage of surgery, complete removal had been achieved in six of the nine patients. The facial nerve was never preserved anatomically.